A Study on the Effect of Housing on Serum Biochemical Parameters of Nellore Lambs (Indian Journal of Animal Production and Management, 2024)
A study was carried out to find out the effect  of housing on serum biochemical parameters of  Nellore Jodipi lambs under tropical environmental  conditions. Thirty weaned Nellore ram lambs of 3-4  months age were selected based on body weight  and randomly divided into three groups of ten  animals each. Temperature and humidity values  were significantly (P
Keywords: Nellore Jodipi lambs; Housing; creatinine; urea; sodium,; potassium; calcium; ALT; AST